Ease‐of‐retrieval effects on procedural justice judgements under conditions of informational and personal uncertainty. Issue 4 (October 2016) - Liang, Juan; Ma, Hongyu; van den Bos, Kees; Cheng, Xiaorong; Wang, Bin; Tong, Hengqing; Guo, Xucheng
Abstract : This study tests whether individuals' reliance on ease‐of‐retrieval processes when forming procedural justice judgements are moderated by informational and personal uncertainty. In Studies 1 and 2 we examined the predicted effects of informational uncertainty. Results indicated that participants in information‐uncertain conditions relied on ease‐of‐retrieval, whereas those in information‐certain conditions relied on content information to make procedural justice judgements. In Study 3 we examined the combined effects of informational uncertainty and personal uncertainty on reliance on ease‐of‐retrieval when forming procedural justice judgements. The findings of Study 3 indicated that personal uncertain participants who were in informational certain conditions based their procedural justice judgements on content information, whereas all other participants based their procedural justice judgements on ease‐of‐retrieval. This is the first paper to demonstrate that the joint effect of informational uncertainty and personal uncertainty on reliance on ease‐of‐retrieval is different from the two uncertainties acting alone.